2013
DOI: 10.1080/21683565.2013.837422
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Agroecology and PAR to Identify Appropriate Food Security and Sovereignty Strategies in Indigenous Communities

Abstract: This article discusses the potential of coupling participatory action research (PAR) with agroecological principles to address food insecurity in indigenous communities. It argues that combining these two approaches can lead to culturally and environmentally appropriate, context-oriented strategies to empower community members and strengthen community food sovereignty and food security. This article draws on a recent study of Mayan communities in the Yucatán State, Mexico, and demonstrates the strengths of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Indigenous knowledge can help build local food system resilience, strengthen food and nutrition security, and help to inform the global debate on improving the sustainability of global food systems [ 52 ]. Studies have identified that agroecological approaches informed by participatory research and indigenous knowledge can help empower communities and increase food sovereignty [ 53 ]. Neglected and underutilized agri-food species also have the potential to generate income for farmers, meet demand in local markets, and contribute to meeting UN sustainability goals [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous knowledge can help build local food system resilience, strengthen food and nutrition security, and help to inform the global debate on improving the sustainability of global food systems [ 52 ]. Studies have identified that agroecological approaches informed by participatory research and indigenous knowledge can help empower communities and increase food sovereignty [ 53 ]. Neglected and underutilized agri-food species also have the potential to generate income for farmers, meet demand in local markets, and contribute to meeting UN sustainability goals [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Southern Spain, researchers associated with the agroecology graduate program at the International University of Andalucía (UNIA), the University of Córdoba (UCO), and the Pablo de Olavide University (UPO), have carried out long-term PAR and agroecology-oriented processes with a variety of farmers [19,27], focusing on issues of ecological production, certification and markets. The Community Agroecology Network (CAN) has collaborated on PAR processes with Santa Clara University and the University of Chapingo, oriented towards food security and sovereignty with coffee farmers in northern Nicaragua [28,29] and Mexico [30], respectively. In Malawi, a collaborative including African, U.S. and Canadian universities and non-government organizations has used the PAR approach to assess agroecological management as a contribution to rural households affected by HIV/AIDs [31,32].…”
Section: Integrating Agroecology and Parmentioning
confidence: 99%
“…Agroecology is itself an alternative way of learning, an educational approach less elitist and pontificating, more akin to citizen science and action research and open to Foucault's ideas about critiquing power relations in the production of knowledge (Bell, M., 2011). It therefore naturally fits with those participatory research methodologies which draw on the work of Paulo Freire (Puttnam, et al, 2014). In all these ways, food initiatives contribute to the quest for a new order in which society and nature explore common principles of self-organisation.…”
Section: 'Commons' As An Abiding Organisational Solutionmentioning
confidence: 97%